Pengaruh Disiplin Dan Kompensasi Terhadap Kinerja Pegawai Pada Kantor Desa Kota Juang - Zainuddin Iba (Jurnal Online Manajemen ELPEI, 2023)
This study aims to determine the effect of discipline and compensation on employee performance at the Kota Juang Village Office. This type of research is associative research. Data collection in this study was carried out through a survey approach with a quantitative descriptive type of research by distributing questionnaires to 30 respondents. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). Data analysis techniques in this study were descriptive analysis, multiple linear regression analysis, hypothesis testing using the partial significant test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The results of this study indicate that discipline and compensation have a positive and significant effect on employee performance